Influnce of Using Photographs in Descriptive Writing to the Students of Nursing - fini widya fransiska fini (Universitas Lancang Kuning, 2020)
The objective of research was to know whether there was any influnces of using photographs in descriptive writing to the students of nursing. In fact, many nurse students still find difficulties in writing. They still find difficulties in expressing what they want to write and how to write. In overcoming those problems, in certain condition to interest them, teacher can use many media to help them producing good written. One of the media is the using of photograph in teaching learning writing. Photograph can make students find ideas in writing and it can help them to make descriptive text when they look the picture. The population was taken from the nurse students of Universitas Muhammadiyah Pringsewu. The writer took two classes for experiment and control. The data collecting technique used the writing test. The teacher gave some topics and the students had to make composition by choosing one of the topic. The analyzing the data, the writer used ttest. After calculated the data, the writer found that was use photographs was x 2ratio = 6.01, and that was without use photographs was x2ratio = 3.93. It can conclude there was any influence of using photographs in descriptive writing to the students of nursing. The writer suggested to English teacher should be use photographs as a media in teaching writing.